PENGARUH PROMOSI, SOCIAL MEDIA MARKETING, DAN BRAND IMAGE TERHADAP KEPUTUSAN PEMBELIAN YANG MENINGKATKAN PELANGGAN PADA TIKET.COM - Prihartono Prihartono; Umi Narimawati; Denok sunarsi (Politeknik APP Jakarta, 2020)
This study aims to determine the effect of promotion, social media marketing, and brand image on purchasing decisions which have an impact on increasing customers at Ticket.Com. In this study using a type of quantitative research with a survey approach with the method used is purposive sampling, with a sample of 96 Ticket.Com customers. The data analysis technique of this research uses PLS software version 3.0 (Partial Least Square) which is a variant-based structural equation model that can simultaneously test the measurement model as well as test the structural model with the research results obtained that Promotion has a positive and significant effect on Purchase Decision with a relationship value of 32.1% (0.321 x 100%). Statistical t value 4.495 > t table 1, 666 and P-value 0.000 <0.05, Social Media Marketing has a positive and significant effect on Purchase Decisions with a relationship value of 67.4% (0.674 x 100%). The t statistic value is 9.474 > t table 1.666 and the P-value is 0.000 <0.05, Brand Image has no effect on Purchase Decision with a relationship value of 4.3% (0.043 x 100%). The t statistic value is 1.033 < t table 1.666 and the P-value is 0.302 > 0.05. Promotion has a positive and significant effect on increasing customers with a relationship value of 48.0% (0.480 x 100%). The t statistic value is 5.082 > t table 1.666 and the P-value is 0.000 <0.05, social media marketing has a positive and significant effect on increasing customers with a relationship value of 35.4% (0.354 x 100%). Statistical t value 3.062 > t table 1.666 and P-value 0.002 <0.05, Brand Image has no effect on Customer Improvement with a relationship value of 1.6% (0.016 x 100%). The value of the t statistic is 0.416 < t table 1.666 and the P-value is 0.677 > 0.05, and the Purchase Decision has no effect on Customer Enhancement with a relationship value.